5-CM-Salophen Schiff Base as an Effective Inhibitor for Corrosion of Mild Steel in 0.5 M HCl. Issue 10 (2nd October 2016) - Seifzadeh, D.; Valizadeh-Pashabeigh, V.; Bezaatpour, A.
Abstract : 5-CM-Salophen Schiff base was examined as an inhibitor for corrosion of mild steel in 0.5 M hydrochloric acid (HCl). The gravimetric data revealed corrosion inhibition effectiveness of the Schiff base even at low concentrations. Polarization measurements showed that the Schiff base is a mixed-type corrosion inhibitor. The polarization resistance (Rp ) increased with increasing the Schiff base concentration. Also, the values of the double-layer capacitance decreased after addition of the inhibitor due to adsorption of the Schiff base on the surface. The inhibition mechanism was investigated by plotting the Langmuir adsorption isotherm and calculating the potential of zero charge (EPZC ) for mild steel samples. Scanning electron microscopy (SEM) analysis confirmed the results of the corrosion tests.